Preferensi Kajian Pekerjaan Sosial pada Skripsi Mahasiswa : Analisis Pola Minat dan Isu Pekerjaan Sosial Kontemporer - Santi, Kanya Eka (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2025)
This study aims to analyze the patterns of topic and field selection in undergraduate social work students’ theses in Indonesia. Using descriptive method, a total of 262 thesis titles from the 2024/2025 academic year were categorized into 14 specialized study fields. Additionally, qualitative data were gathered from 61 students via questionnaires to explore their reasons for topic selection, suggestions on subject-specific courses, and experiences in thesis supervision. The findings reveal that child-related social work is the most preferred field (41.4%), followed by poverty, aging, disability, and education. Key factors influencing topic choice include personal interest, practical experience, ease of data access, and social relevance. However, topic repetition and limited exploration of novel research ideas are still common. These findings highlight the need for curriculum review, improved field placement systems, and more contextual supervision strategies to support the diversification and originality of student research. This study offers practical input for curriculum development, thesis supervision planning, and the formulation of a research roadmap aligned with contemporary social issues.